Ameliorative Effect of Cactus (Opuntia ficus indica) Extract on Lithium-Induced Nephrocardiotoxicity: A Biochemical and Histopathological Study. (10th December 2017) - Saad, Anouar ben; Rjeibi, Ilhem; Ncib, Sana; Zouari, Nacim; Zourgui, Lazhar
Abstract : Opuntia ficus indica (family Cactaceae) is used in the treatment of a variety of conditions including metal-induced toxicity. The study reports the protective effects of Opuntia ficus indica (CCE) against lithium carbonate-induced toxicity in rats. Nephrocardiotoxicity was induced in male Wistar rats by single dose of lithium carbonate (25 mg/kg b.w twice daily for 30 days). Aqueous extract of Opuntia ficus indica was administered at the dose of 100 mg/kg of b.w by gavage for 60 days. Obtained results revealed that administration of lithium carbonate caused a significant increase in serum creatinine, uric acid, and urea levels. Additionally, a significant decrease in the level of renal and cardiac SOD, CAT, and GPx activities was associated with a significant increase of MDA levels in lithium carbonate group more than those of the control. However, the treatment of experimental rats with CCE prevented these alterations and maintained the antioxidant status. The histopathological observations supported the biochemical evidences of nephrocardioprotection. CCE supplementation could protect against lithium carbonate-induced renal and cardiac injuries in rats, plausibly by the upregulation of antioxidant enzymes and inhibition of MDA to confer the protective effect.